2019
DOI: 10.1002/pds.4803
|View full text |Cite
|
Sign up to set email alerts
|

Validity of ICD‐9 and ICD‐10 codes used to identify acute liver injury: A study in three European data sources

Abstract: Purpose Validating cases of acute liver injury (ALI) in health care data sources is challenging. Previous validation studies reported low positive predictive values (PPVs). Methods Case validation was undertaken in a study conducted from 2009 to 2014 assessing the risk of ALI in antidepressants users in databases in Spain (EpiChron and SIDIAP) and the Danish National Health Registers. Three ALI definitions were evaluated: primary (specific hospital discharge codes), sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Liver function was determined each follow up year by analysing serum levels of alkaline phosphatase (ALP), alanine transaminase (ALT) and gamma-glutamyl transpeptidase (GGT). Liver function was considered abnormal when after baseline, at least one of the values was as follows: ALP >2x129 IU/L; ALT>5x41 IU/L (men) or ALT>5x33 IU/L (women); GGT>61 IU/L (27).…”
Section: Liver Functionmentioning
confidence: 99%
“…Liver function was determined each follow up year by analysing serum levels of alkaline phosphatase (ALP), alanine transaminase (ALT) and gamma-glutamyl transpeptidase (GGT). Liver function was considered abnormal when after baseline, at least one of the values was as follows: ALP >2x129 IU/L; ALT>5x41 IU/L (men) or ALT>5x33 IU/L (women); GGT>61 IU/L (27).…”
Section: Liver Functionmentioning
confidence: 99%
“…The corresponding ICD‐10 code (K71.0, toxic liver disease with cholestasis) would presumably be more specific, but previous validation studies using this ICD‐10 code were not available. In the current study (see supplemental tables) and in the parent study, the PPVs of the ICD‐10 code K71.0 ranged between 50% and 80%. Although it is important to keep in mind that in both studies ALI rather than DILI was the outcome of interest, a recently published systematic review and meta‐analysis including 29 studies validating ALI or DILI showed a pooled PPV estimate for ALI of 13.4% (95% CI, 6.1%‐22.8%) and for DILI of 15.3% (95% CI, 9.5%‐22.2%) …”
Section: Discussionmentioning
confidence: 53%
“…Three of five databases participating in the agomelatine PASS were amenable for direct validation of cases within the respective database . The PPVs ranged from 60% to 84% for the primary PASS outcome (specific end point after exclusion of cases with known competing causes of ALI) . Case numbers in two of these databases were very small, explaining in part the large variability in observed PPVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential cases were adjudicated by trained clinicians based on review of information abstracted from medical records. This information included timing and results of liver enzymes and information on presence or absence of excluding conditions [ 33 ]. Thus, the clinical reviewers were adjudicating whether the individual potential cases met the study definition criteria of ALI and whether excluding conditions were present, not whether they met criteria for causality between antidepressant use and liver injury.…”
Section: Methodsmentioning
confidence: 99%